Didactical Design Based on Sharing and Jumping Tasks on Reaction Rate Law - Sazaliana, Ade; Hendayana, Sumar; Supriatna, Asep; Nofri Yuhelman (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
In improving the quality of learning, it is necessary to develop a learning design that can facilitate the characteristics of students. The didactical design can facilitate the characteristics of students through sharing and jumping tasks. Sharing task is used to facilitate slow learner while jumping task is used to facilitate fast learner. Jumping task is not only beneficial for students with high academic ability, but also provides benefits for students with low academic ability. The purpose of this study is to develop the didactical design based on sharing and jumping tasks to enhance learning quality on the topic of reaction rate low. The research method used is didactical design research (DDR). Didactical design consisted of three steps i.e. (a) analysis of didactical situation before learning (prospective), (b) analysis of didactical situation during learning (metapedadidactical), and (c) analysis of didactical situation after learning (retrospective). The data was collected by test, observation, interview, documentation and recording (audio and video). The result showed that the didactical design on the topic of reaction was valid